Financial crisis and International reserves - Joshua Aizenman (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
Prepared for the 'Princeton Encyclopedia of the World Economy', Princeton University Press.
Keywords: 330; Finanzmarktkrise; Kapitalmobilität; Internationaler Finanzmarkt